2011
DOI: 10.1016/j.crma.2011.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Can a traveling wave connect two unstable states? The case of the nonlocal Fisher equation

Abstract: Presented by the Editorial BoardThis Note investigates the properties of the traveling waves solutions of the nonlocal Fisher equation. The existence of such solutions has been proved recently in Berestycki et al. (2009) [3] but their asymptotic behavior was still unclear. We use here a new numerical approximation of these traveling waves which shows that some traveling waves connect the two homogeneous steady states 0 and 1, which is a striking fact since 0 is dynamically unstable and 1 is unstable in the sen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
64
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(65 citation statements)
references
References 7 publications
1
64
0
Order By: Relevance
“…Suppose that supp N c ∩ (0, +∞) = ∅ and let φ(t) be a positive monotone wavefront. Set y(t) = 1 − φ(t) and let σ * be defined as in (20). Then χ + (σ * , c, τ ) is finite and non-negative.…”
Section: Necessity Of the Condition Imposed On χ + (Z C τ )mentioning
confidence: 99%
“…Suppose that supp N c ∩ (0, +∞) = ∅ and let φ(t) be a positive monotone wavefront. Set y(t) = 1 − φ(t) and let σ * be defined as in (20). Then χ + (σ * , c, τ ) is finite and non-negative.…”
Section: Necessity Of the Condition Imposed On χ + (Z C τ )mentioning
confidence: 99%
“…Berestycki et al [8] proved that equation (1.4) admits traveling wave solutions connecting 0 to an unknown positive state for all speeds c ≥ c * = 2 √ μ and there exists no such traveling wave solution with the wave speed c < 2 √ μ. Then, Nadin et al [21] showed that the unknown state is just the equilibrium 1 for some traveling wave solutions. Fang and Zhao [10] further gave a sufficient and necessary condition for the existence of monotone traveling waves of equation (1.4) connecting two equilibria 0 and 1.…”
Section: Introductionmentioning
confidence: 99%
“…In more sophisticated contexts (reaction–diffusion systems, nonlocal equations, etc. ), propagating terraces with unstable intermediate states are observed numerically [, among others]. Rigorous analytical studies are, however, very difficult and have only been carried out in simple cases and with Heavyside‐like or compactly supported initial data .…”
Section: Introductionmentioning
confidence: 99%